Desain Situs Web yang Responsif berdasarkan Strategi Agile sebagai Pendukung Pemasaran Destinasi Wisata - Wasino Wasino; Dyah Erny Herwindiati; Ignatius Roni Setyawan; Haris Maupa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Digital innovation in business activities is essential through digital technologies such as websites. The website is a means of marketing tourist destinations that can bring tourists to find exciting information about selected tourist destinations. There is a problem that tourism websites, resulting from some studies, are not implemented for unrestricted use by tourists and tourism industry stakeholders. In addition, there is a lack of responsive and tourist-centric design and interactivity in developing tourism websites. The purpose of this study is to fix these problems by presenting a tourist destination website that is designed responsively. The website is also carefully crafted to improve service performance to support the digital marketing of tourist destinations. The website is designed to be used to manage tourist destinations based on the category, region, and popularity of the tourist destination. A tourism web system with good management of tourist destinations can help ease tourists' visits. This tourist destination website is built responsively using fluid grid layouts, flexible images and media, media queries, and screen resolution techniques. The use of data that has gone through the normalization stage by eliminating partial and transitive dependencies to avoid the occurrence of data anomalies. After testing, the tourist destination website is implemented through the www.pesonajawa.com page.